THE EFFECT OF GOVERNMENT HEALTH PROGRAMS ON PEOPLE'S WELFARE IN THE CITY OF MEDAN - Johnson Pasaribu (The American Journal of Interdisciplinary Innovations and Research, 2024)
The formulation of the problem that arises from this research is how the variables of the role of health workers and social status affect the welfare of the people of Medan City through income as an intervening variable. The subject of this research is the people of Medan City (residents) of Medan City, where the variables in this study are independent variables, namely the role of health workers and social status, dependent variables, namely community welfare variables and intervening variables are income variables. The results of data analysis used using SEM analysis using SMART PLS 3.0 software. as for data collection techniques with questionnaires and observational studies. The research method uses a quantitative descriptive method of data analysis using the structural equation model (SEM) method, where the results of data processing with the SEM method are carried out with the PLS 4.0 application. From the results of the study, the conclusion is that partially, only the variable role of health workers has an effect on community welfare and affects community income. Simultaneously, the variables of the role of health workers and social status affect the improvement of community welfare through the variable of community income as an intervening variable. From the results of this study, the conclusion that exists, namely partially partially only the variable role of health workers that affects community welfare and affects community income. Simultaneously, the role of health workers and social status variables affect the improvement of community welfare through the variable of community income as an intervening variable.